KEDUDUKAN HUKUM MINUTA AKTA NOTARIS DALAM TINDAK PIDANA PEMALSUAN DI KOTA PADANG - , Fakhlisa Hesti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study was to determine the basis for consideration minuta Notary deed can be used as evidence in a criminal case, to find out how making procedures minuta Deed as evidence in a criminal case, to know the constraints the police investigators in solving the crime of counterfeiting minuta contained in the Notary deed. Research conducted is sociological empirical research, that is/was done against the issues having regard to the legal norms and legislation as well as the opinion of experts with regard to theoretical concepts to next viewed its application in field, how data collection is carried out by research field which use guidelines interviews and research library use studies documents. Can act as Minuta means of proof in criminal cases, because of the affidafit notary minuta deed made pursuant to the provisions of the procedure or procedures for making Act, then it can be used as a means of proof in criminal cases and has the power of proof that perfect, if there is a procedure that is not met and the procedures are not met it can be demonstrated then the deed with court proceedings can be expressed as an act which has the power of proof as a deed under hand.Retrieval procedure affidafit notary minuta as evidence in criminal matters should be based on the UUJN of article 66, beginning with the Assembly the Area Supervisor has the authority to inspect the notary with respect to the request of the investigator, public prosecutor or the judge, after examination, the end result is poured by the MPD's in the form of a Decree, contain may provide consent or refuse the request, the public prosecutor or the investigating judge. From this new decree Investigators can start the examination of such deed minuta. Constraints contained in the resolution of criminal matters Act of counterfeiting minuta is a Police Investigator in the case of Calling a notary, the seizure and proof, yet one Deed Minuta perception among Investigators that Act on the code of criminal procedure with The Notary and the MPW MPD either act on UUJN, in which case it applies the principle of Lex specialists derogat legi generali where the code of criminal procedure as applicable law be excluded by the nature of General UUJN who was a law that is specifically.